The association between arrival potassium and 30-day survival following resuscitation from out-of-hospital cardiac arrest: a retrospective cohort study - Byrne, Christina; Krogager, Maria Lukacs; Kragholm, Kristian; Pareek, Manan; Mohr, Grimur Høgnason; Ringgren, Kristian Bundgaard; Wissenberg, Mads; Riddersholm, Signe; Wolder, Martin; Folke, Fredrik; Gislason, Gunnar; Køber, Lars; et al. (Scandinavian journal of trauma, resuscitation and emergency medicine, 2025)
Background It is unknown whether there is an association between initial serum potassium level and short-term survival in out-of-hospital cardiac arrest (OHCA) survivors. The aim of this study was to describe potential associations between first recorded potassium level and 30-day survival in patients surviving OHCA. Methods We identified 4,894 patients who had return of spontaneous circulation (ROSC) at hospital arrival, and a registered post-OHCA serum-potassium value, using Danish nationwide registry data from 2001–2019. Potassium values were divided into seven predefined levels: < 2.5, 2.5–2.9, 3.0–3.4, 3.5–4.6, 4.7–5.5, 5.5–6.0, > 6.0 mmol/L. Thirty-day survival was estimated using a multivariable Cox regression (reference normokalemia 3.5–4.6 mmol/L). The multivariable model included age, sex, Charlson comorbidity index (including chronic kidney disease), witnessed status, performance of bystander cardiopulmonary resuscitation (CPR) and first registered heart rhythm. Results Over the 30-day follow-up period, survival rates in the seven strata were as follows: 25 (51.0%), 119 (53.6%), 512 (65.4%), 1,631 (57.9%), 220 (32.7%), 34 (22.8%), and 46 (22.7%), respectively. Thirty-day survival was significantly lower for all groups with hyperkalemia compared with normokalemia: 4.7–5.5 mmol/L: (average risk ratio (RR): 0.72, 95% confidence interval (95% CI): 0.66–0.78); 5.5–6.0 mmol/L: (average RR: 0.60, 95% CI: 0.47–0.73); > 6.0 mmol/L: (average RR: 0.56, 95% CI: 0.46–0.66). Survival did not differ significantly in patients with hypokalemia compared with normokalemia. Conclusions In OHCA survivors, hyperkalemia was associated with reduced 30-day survival compared with normokalemia, independent of age, sex, comorbidity burden and pre-hospital OHCA-characteristics. Conversely, hypokalemia was not associated with reduced 30-day survival.